Pemberdayaan Kemandirian Masyarakat Melalui Pemeliharaan Kambing pada Komunitas Marbot di Kecamatan Metro Barat Kota Metro - Subandi Subandi; Yosep Aspat Alamsyah; Ahmad Fauzan; Guntur Cahaya Kesuma (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2020)
The increasing number of goat rearing communities in the community will be able to realize economic independence. The aim of this assistance is to produce community economic clusters that are able to foster a creative economy in fostering community independence. This empowerment method with the ABCD (Asset-Based Community Development) approach with this method is able to describe the assets owned by the community that is able to be developed. The marbot community is given assistance with the capital of the female goat capital, the goat parent is given by the partners from the collection of alms donation (ZIZ) with a mutual cooperation management system. With assistance can be concluded 1) Increase community understanding about breeding goats (graiding) 2) Increasing community understanding about raising dairy goats, 3) Improved skills in making milk from Etawa (PE) derivatives, 4) Increased skills in making compost. The impact of the community is the emergence of an entrepreneurial spirit, the formation of micro-business clusters by mutual cooperation, and economic independence towards the welfare of society.